The utilization of library resources by undergraduates of Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria (2012)
This is a study on the usage of library resources by undergraduates of a state-owned university in Nigeria. The survey method of research was employed via the questionnaire instrument to elicit information on the adequacy of operational time; various retrieval access options; availability, adequacy and relevance of the materials; consultations of the different resources in the library; availability and adequacy of reprographic services; and the type of rapport between library staff and the students. Using frequency counts, percentages and tables to analyze responses, it was discovered that the resources of the library were under-utilized due mainly to inadequate user instructions, insufficient operational hours per day, and inadequate support facilities like reprography. However, the library resources are fairly adequate for undergraduate scholarship and there exists cordial relationship between library staff and students. The need to educate students on library use skills through orientations and library instruction programmes is emphasized while library staff should also be trained in the modern techniques of library management to enhance service delivery